LEGAL PROTLEGAL PROTECTION FOR CUSTOMERS OF CECTION FOR CUSTOMERS OF CONVENTIONAL INSURANCE COMPANIES THAT CONVERT INTO SHARIA GENERAL INSURANCE - Manurung, Qhairul Fadly (Awang Long Law Review, 2023)
The problem of legal protection for customers who are members of insurance companies that carry out conversion from conventional insurance to general Sharia Insurance has indications of the emergence of legal problems. This is because the customer must decide whether to renew the policy contract with Adira Insurance for conventional general insurance products or change the policy contract to a Sharia General Insurance Policy. The research method used is normative juridical. The purpose of this study is to answer about legal protection for customers who are members of insurance companies that carry out conventions from conventional insurance to general Sharia Insurance. The results showed that its urgency to find a format and solution from the company for all former clients of PT Zurich Insurance Indonesia so that clients who do not want to transfer their policies to Sharia General Insurance have clear certainty and legal protection.